Impact of sole and integrated use of plant residues as soil amendments on tomato (Lycopersicum esculentum Mill.) production - Kekere , Otitoloju; Mary, Oloruntoba Tosin; Akinbuwa, Olumakinde (Journal of Pure and Applied Agriculture, 2023)
Poor soil condition is a major problem of tomato production in Nigeria. Soil amendment with plant-based materials is an integral part of organic agriculture; hence an experiment was conducted on sole and integrated use of plant residues as soil amendments in tomato cultivation and production.